Induction of Apoptosis and Decrease of Autophagy in Colon Cancer Cells by an Extract of Lyophilized Mango Pulp (2023)
ABSTRACT: Previous studies have indicated that mango fruit has a chemopreventive capacity against colorectal cancer cells. The objective of this research was to evaluate the effect of an aqueous extract of lyophilized mango pulp (LMPE) on colon adenocarcinoma cells (SW480) and their metastatic derivatives (SW620) death and cellular invasion. DNA fragmentation was assessed by TUNEL assay; autophagy and expression of DR4 and Bcl-2 by flow cytometry; the expression of 35 apoptosis-related proteins and of matrix metalloproteinases 7 and 9 by immunodetection; and the invasive capacity of the cells by Boyden chamber. The results showed that LMPE at 30 mg/mL and 48 h of exposure results in DNA fragmentation and apoptosis in SW480 (p < 0.001) and SW620 (p < 0.01) cells. Additionally, LMPE decreased autophagy in the SW480 and SW620 cell lines (p < 0.001), which could sensitize them to the DNA damage generated by LMPE. The LMPE did not modulate the expression of matrix metalloproteinases 7 and 9, nor did it affect cellular invasion processes in the SW480 and SW620 cell lines. In conclusion, LMPE induces apoptosis and decreases autophagy in SW480 and SW620 cells.